“Ele vai negar tudo”:: O estudo interacional de uma estória de violência doméstica contra a mulher narrada em entrevista de pré-mediação familiar judicial - Gago, Paulo Cortes; de Oliveira, Maria do Carmo Leite; Penna, Áida Silva; Pereira, Maria de Lourdes; de Paula, Vanderlei Andrade (Language and Law / Linguagem e Direito, 2022)
In this article, we study the narrative of a woman, allegedly the victim of gender-based violence, produced spontaneously in a legal family pre-mediation interview, in a child custody lawsuit. In a qualitative research work, in light of the theoretical-methodological framework of Conversation Analysis, we analyzed moments of this narrative as sequential objects, arranged in turns of talk-in-interaction. We describe the types of violence narrated, the way they occurred, and the actions of the social actors involved. Furthermore, we relate the narrative episodes that make up the plot to the `Maria da Penha' Law and the cycle of violence. The results point to a complex network of personal and institutional relationships that deal with violence against women, in which everyone is an actor, whether in combat or in the perpetuation of the cycle of violence. We relate the micro-interactional results to macro-social and public policy issues.